2020
DOI: 10.1097/scs.0000000000007167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Biomechanical Stiffness of Titanium and Sonic Weld RX Osteofixation Systems for Monoblock Zygomaticomaxillary Complex Fractures

Abstract: Resorbable osteosynthesis systems are widely used for the fixation of zygomaticomaxillary complex (ZMC) fractures instead of titanium systems, because they do not have postoperative hardware-related complications. However, the strength of conventional resorbable systems is inferior to that of titanium systems. Recently, ultrasound-aided resorbable osteosynthesis systems, which have higher fixation than conventional resorbable osteosynthesis systems, have become available.The purpose of this study was to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These results are in the same direction with Dubina et al, 2013 (12) who reported that neither of their cases met a change transplant and implant con guration, nor displaced plates and pins. The rigid xation of bone fragments was observed in their study, over and above Iwanaga et al, 2021 (13) stated in his study when compared the biomechanical stiffness of titanium and SonicWeld Rx ® osteo xation systems for monoblock zygomaticomaxillary complex fractures that there was no statical difference between the two systems.…”
Section: Fracture Reduction and Pin Holes Ossi Cationmentioning
confidence: 68%
“…These results are in the same direction with Dubina et al, 2013 (12) who reported that neither of their cases met a change transplant and implant con guration, nor displaced plates and pins. The rigid xation of bone fragments was observed in their study, over and above Iwanaga et al, 2021 (13) stated in his study when compared the biomechanical stiffness of titanium and SonicWeld Rx ® osteo xation systems for monoblock zygomaticomaxillary complex fractures that there was no statical difference between the two systems.…”
Section: Fracture Reduction and Pin Holes Ossi Cationmentioning
confidence: 68%
“…), alloys, as well as the more commonly used titanium mesh (TM) and the composites therein have been applied to clinical practice. Besides, in recent years more advanced resorbable materials with sufficient strength and moderate degradation rate have emerged, which is especially meaningful in the craniofacial bone repair species of pediatric and adolescent patients, considering the development of craniofacial bone in growing children. The main absorbable materials currently used in craniomaxillofacial surgery are aliphatic polyesters, such as RapidSorb (PLLA), Polymax (P­(L/DL) LA), etc. Fewer resorbable products with osteoconductive activity, such as PLLA-μHA complexes (FIXSORB MX), are available. In recent years, modifications of titanium mesh, , biodegradable alloys such as magnesium alloys, , addition of coatings with antimicrobial or biocompatible properties on the surface of the alloy, materials that can deform with children’s bone development, , and other patented designs try to make up for the shortcomings of the existing materials on the market, and resorbable composites that combine the advantages of a variety of materials themselves have become a current research hotspot and a trend in the development of bone repair materials.…”
Section: Materials Evaluation and Translational Researchmentioning
confidence: 99%